Interfacial Post‐Treatment for Enhancing the Performance of Printable Carbon‐Based Perovskite Solar Cells. Issue 2 (19th July 2019) - Liu, Tongfa; Wang, Zheng; Lou, Lingyun; Xiao, Shuang; Zheng, Shizhao; Yang, Shihe
Abstract : The interface between the perovskite layer and carbon electrode is important for printable carbon‐based perovskite solar cells (PSCs) to improve the power conversion efficiency (PCE) and device stability. A series of acetate salts are employed to in situ post‐modify the interface between the perovskite layer and carbon electrode for printable carbon‐based PSCs by the post‐treatment method. Cesium acetate (CsAc) is identified to enhance the average PCE from 12.6% to 15.3%. The stabilized output PCE reaches 15.6%, and the highest open‐circuit voltage ( V OC ) is 1.1 V, representing a new milestone in increasing the ratio of V OC / E g ( E g : bandgap of perovskite) to be 0.67 for the printable carbon‐based PSCs without hole transporting materials. Moreover, the device stability in air is also improved by CsAc post‐modification. The improved performance is attributed to the better matching of energy levels of the perovskite layer with a carbon electrode and reduced defect density in the perovskite layer via in situ produced methylammonium acetate and ion replacement. This simple and effective CsAc post‐treatment method opens a new promising direction for developing scalable carbon‐based PSCs. Abstract : The power conversion efficiency of the carbon‐based perovskite solar cells is enhanced by 21.4% simply by interfacial post‐treatment with cesium acetate. The nonencapsulated device can remain stable for 4 months without observable degradation. The improved performance is attributed to the better matched energy levels and the reduced defect density.